تکنیک ءُ آئی ءِ دروشم: technique and its kinds - Dad, A.R (Hanken, 2009)
The techniques and styles of the fiction have been introduced in the western world long before. Namely from centuries but these techniques are new in the Blaohci fiction. The aim of this paper is to discuss the deferent styles and techniques of fiction and other form of literature. These styles and techniques of fiction will be introduced first time in the Balochi fiction and the terminologies regarding the techniques of fiction will also be introduced to find out the vastness of Balochi fiction.